Power Save Protocol Using Chain Based Routing - Nguyen, Thanh Tung (International Conference on Context-Aware Systems and Applications, 2017)
International Conference on Context-Aware Systems and Applications ICCASA 2012: Context-Aware Systems and Applications pp 183-191